Advanced Radiation Sources and Applications Proceedings of the NATO Advanced Research Workshop, held in Nor-Hamberd, Yerevan, Armenia, August 29 - September 2, 2004 - Wiedemann, Helmut; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This book covers latest development in theory and experiments of unconventional radiation production. Specifically, the generation of Tera-Hertz and X-ray radiation from low energy electron beams in the form of Channeling, Transition, Diffraction, Cherenkov, Smith-Purcell, PXR and Crystalline Undulator Radiation are presented. Material characteristics like thin targets, curved or bend crystals, inhomogeneous and left handed materials, multilayers as well as stimulation by external radiation are covered to demonstrate their influence in these processes. Novel ideas are offered on the use of such radiation in detectors and particle beam monitor development with improved energy or time resolution. The book assumes some familiarity of the reader with theoretical concepts underlying these phenomena and is therefore of primary use to the practicing scientist. More fundamental discussions of these phenomena can be found in the 2002 monograph "Electron-Photon Interaction in Dense Media" within the NATO Science Series II: Mathematics, Physics and Chemistry - Vol. 49.
OVERVIEW OF ADVANCED PHOTON SOURCES AND THEIR APPLICATIONS -- DYNAMICAL EFFECTS FOR HIGH RESOLUTION PARAMETRIC X-RADIATION -- DIFFRACTION, EXTRACTION AND FOCUSING OF PARAMETRIC X-RAY RADIATION, CHANNELING RADIATION AND CRYSTAL UNDULATOR RADIATION FROM A BENT CRYSTAL -- CHOICE OF OPTIMAL TARGET FOR MONOCHROMATIC TUNABLE X-RAY SOURCE BASED ON LOW-ENERGY ACCELERATOR -- POLARIZED RADIATION FROM ELECTRONS AT OFF-AXIS CRYSTAL ORIENTATION -- RADIATION EMITTED FROM RELATIVISTIC PLANAR CHANNELED POSITRONS -- RADIATION PRODUCED BY FAST PARTICLES IN LEFT-HANDED MATERIALS (LHM) AND PHOTONIC CRYSTALS (PHC) -- POLARIZATION EFFECTS ON ELECTROMAGNETIC PROCESSES IN ORIENTED CRYSTALS AT HIGH ENERGY -- CALCULATION OF PLANAR CHANNELING RADIATION PRODUCED BY 20 MEV ELECTRONS IN QUARTZ -- CHANNELING AT EXTREMELY HIGH BUNCH CHARGES AND SOLID STATE PLASMA ACCELERATION -- TRANSITION RADIATION BY RELATIVISTIC ELECTRONS IN INHOMOGENEOUS SUBSTANCE -- IMAGE OF OPTICAL DIFFRACTION RADIATION (ODR) SOURCE AND SPATIAL RESOLUTION OF ODR BEAM PROFILE MONITOR -- SPONTANEOUS AND STIMULATED PHOTON EMISSION IN CRYSTALINE UNDULATORS -- ACCELERATOR TESTS OF CRYSTAL UNDULATORS -- SURFACE EFFECTS ON A DIAMOND TARGET AT NON-LINEAR EMISSION OF SPONTANEOUS RADIATION FROM 4.3 GEV ELECTRONS -- X-RAY TRANSITION AND CHERENKOV RADIATION PRODUCED BY HIGH-ENERGY PARTICLES IN MULTILAYERS AND THEIR APPLICATIONS -- X-RAY CHERENKOV RADIATION -- ON X-RAY SOURCES BASED ON CHERENKOV AND QUASI-CHERENKOV EMISSION MECHANISMS -- INVESTIGATION OF FAR-INFRARED SMITH-PURCELL RADIATION AT THE 3.41 MEV ELECTRON INJECTOR LINAC OF THE MAINZ MICROTRON MAMI -- RADIATION BY RELATIVISTIC ELECTRONS IN THIN TARGETS AND AT COLLISIONS WITH SHORT BUNCHES OF RELATIVISTIC PARTICLES -- RING X-RAY TRANSITION RADIATION DETECTORS ON THE BASIS OF CHARGE COUPLED DEVICE ARRAY -- HIGH ANALIZING POWER GAMMA POLARIMETER -- PROPOSAL FOR A PHOTON DETECTOR WITH PICOSECOND TIME RESOLUTION -- FEMTOSECOND DEFLECTION OF ELECTRON BEAMS IN LASER FIELDS AND FEMTOSECOND OSCILLOSCOPES -- NOVEL FAST-ACTING SCINTILLATION DETECTORS FOR WIDE ENERGY RANGE APPLICATIONS -- POROUS DIELECTRIC DETECTORS OF IONIZING RADIATION -- VIBRATING WIRE SCANNER/MONITOR FOR PHOTON BEAMS WITH WIDE RANGE OF SPECTRUM AND INTENSITY -- NUCLEAR ASTROPHYSICS MEASUREMENTS ON ELECTRON LINEAR ACCELERATOR -- A COMBINED HIGH ENERGY MOELLER AND COMPTON POLARIMETER -- EXPERIMENTAL STUDIES OF POSITRON SOURCES USING MULTI-GEV CHANNELLED ELECTRONS AT CERN(a) AND KEK(b) -- SOME RESULTS ON MICROANALYSIS OF GOLD USING MICRO-XRF AT THE ANKA - KARLSRUHE SYNCHROTRON RADIATION FACILITY -- INELASTIC PHOTON-ELECTRON COLLISIONS WITH POLARIZED BEAMS -- IMPACT PARAMETER PROFILE OF SYNCHROTRON RADIATION -- STATUS AND HIGHLIGHTS OF THE CANDLE PROJECT -- NON-LINEAR BEAM DYNAMICS STUDY IN LOW EMITTANCE STORAGE RINGS -- STUDY OF THE MULTI-LEVEL EPICS BASED CONTROL SYSTEM FOR CANDLE LIGHT SOURCE -- MAIN APPROACHES TO THE COOLING SYSTEM FOR THE CANDLE LIGHT SOURCE -- PROPOSED FIRST BEAMLINES FOR CANDLE -- POWER CONVERTERS FOR CANDLE LIGHT SOURCE -- RING X-RAY TRANSITION RADIATION DETECTORS ON THE BASIS OF CHARGE COUPLED DEVICE ARRAY.
Keywords: PHYSICS; PARTICLE ACCELERATION; ELECTROMAGNETISM; LASER PHYSICS; PHYSICS; PARTICLE ACCELERATION AND DETECTION, BEAM PHYSICS; ELECTROMAGNETISM, OPTICS AND LASERS; LASER TECHNOLOGY AND PHYSICS, PHOTONICS